Use of nanomodified polypropylene net in surgical treatment of umbilical hernias combined with diastasis of straight muscles - Lutkovskyi, Ruslan (Journal of Education, Health and Sport, 2020)
Aloplasty of umbilical hernias (UH) with diastasis of rectus abdominis (DRA) of using modified polypropylene mesh antiseptic and an by carbon nanotubes, buth this is accompanied by a fairly high freguency of postoperative complications from the postoperative wound. In our view, the use of a nanomodified polypropylene mesh modified by carbon nanotubes and an antiseptic of polyhexamethleneguanidme chloride the results of surgical treatment UH of DRA. Aim – to improve the results of surgical treatment of umbilical hernias with diastasis of rectus abdominis. Materials and methods. The analysis of surgical treatment of 118 patients with UH of DRA of has been performed. Depending on the type of mesh used during surgical treatment, patients were divided into 2 groups. In 59 (50%) of Group I patients, using modified polypropylene mesh antiseptic and an by carbon nanotubes. In the 2ndgroup, 59 (50%) patients using classic polypropylene mesh. Results and discussion. Statistically significant results were obtained in patients of Group I compared to Group II: seroma was in 12 (20.3±1.2%) in Group II compared to 2 (3.4±0.3%) in Group I (p<0.05), respectively, the suppuration of the postoperative wound – 2 (3.4±0.3%) to 0% (p<0.05). The terms of stay of patients of group II on inpatient treatment – 12,3±2,2 days group II – 7,5±1,5 days. Long-term results: chronic pain in the abdominal wall in 6 – 8 months after surgery was observed in 2 (3.4±0.3)% patients in group II and in 1 (1.8±0.3%) group I (p>0.05), recurrences of hernia were found in 6 (5.9±0.5%) patients of group II, in group I – in 1 (0.9±0.2)% (p<0.05). Conclusion. Surgical treatment of UH of DRA using modified polypropylene mesh antiseptic and an by carbon nanotubes the use of the classical polypropylene mesh, namely, reducing the freguency of seroma from 20.3±1.2% in the II group of patients to 3.4±0.3% in group I, respectively, suppurations of postoperative wounds – from 3.4±0.3% to 0%, inflammatory infiltrates – from 3.4±0.3% to 0%, chronic postoperative pain – from 3.9±0.4% to 0%, recurrence of hernia–from 5.9±0.5% to 0.9±0.2%.